Developing a therapeutic app based on the emotional Stroop task for objective discovery of daily life issues for people with ADHD - S. Schoenmakers; S. H. Bos; W. A. Ijsselsteijn (Frontiers in Psychology)
Pinpointing the most urgent problem to start treatment on in therapy for people with ADHD is a subjective and time-consuming process. To improve this process, we designed a proof-of-concept for an application that can identify daily life issues that cause negative mental load. Through several modified emotional Stroop-tasks, we show that people with ADHD respond slower to negative emotions and daily life issues related to ADHD, compared to neurotypicals. Negative emotions and social issues were especially prevalent in the ADHD participants. The application highlighted two to five issues per participant. This could indicate that these topics cause the highest mental load in the participant, and need attention first from a therapist. Using this application in a therapeutic context could deliver a more objective, personalized, traceable and efficient therapy for daily-life issues in ADHD.